TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Physics and fiber optic data dual-driven dynamic prediction method for dam foundation settlement - Heming Han; Fusheng Zha; Long Xu; Bo Kang; Xuedong Zhang; Guangqing Wei; Hao Li; Bin Shi (Engineering Geology, 2025)

Predicting the flavor potential of green coffee beans with machine learning-assisted visible/near-infrared hyperspectral imaging (Vis-NIR HSI): Batch effect removal and few-shot learning framework - Minping Wu; Zhuangwei Shi; Haiyu Zhang; Rui Wang; Jiayi Chu; Shao Quan Liu; Heming Zhang; Hai Bi; Weihua Huang; Rui Zhou; Chenhui Wang (Food Control, 2025)

A local scour self-sensing method for offshore wind power monopile based on ultra-weak Fiber Bragg Grating - Heming Han; Bin Shi; Fusheng Zha; Guangqing Wei; Zhihao Meng; Daoyuan Tan (Ocean Engineering, 2025)

In situ synthesis of MIL-101 on carboxyl-functionalized SBA-16: Preparation and catalytic performance in the Knoevenagel condensation reaction under mild conditions - Chunlai Liu; Na Wang; Zelin Meng; Mingyang Song; Heming Zhao; Jianglei Hu; Fengwei Shi (Journal of Environmental Chemical Engineering, 2025)

Rapid identification of defects in doped organic crystalline films via machine learning-enhanced hyperspectral imaging - Lijiao Wu; Wei Wang; Zhuangwei Shi; Haiyu Zhang; Lianbao Ke; Xiaohong Liang; Detian Tian; Heming Zhang; Hai Bi; Wangqiao Chen; Guofu Zhou (Chemical Engineering Journal, 2025)

Identification of the CYP gene family: insights into carotenoid metabolism associated with red shell in Meretrix meretrix - Heming Shi; Lulu Fu; Yinghui Dong; Zhihua Lin; Jilin Xu; Hanhan Yao (Aquaculture International, 2025)

Shear deformation calculation of landslide using distributed strain sensing technology considering the coupling effect - Lei Zhang; Yifei Cui; Honghu Zhu; Han Wu; Heming Han; Yan Yan; Bin Shi (Landslides, 2023)

Ultra-weak FBG sensing for identification and analysis of plastic zone of soil caused by supported excavation - Heming Han; Bin Shi; Yaowen Yang; Cheng-Cheng Zhang; Lei Zhang; Guangqing Wei (Engineering Geology, 2023)

Characterization and Function Analysis of β, β-carotene-9′, 10′-oxygenase 2 (BCDO2) Gene in Carotenoid Metabolism of the Red Shell Hard Clam (Meretrix meretrix) - Lulu Fu; Heming Shi; Wenfang Dai; Hanhan Yao; Yongbo Bao; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2021)
The relationship between carotenoid and shellfish shell color has gained increasing attention. β, β-carotene-9′,10′-oxygenase 2 (BCDO2) is a key enzyme in animal carotenoid metabolism, and its accumulation affects the change in body color, as demonstrated in mammals, birds, and fish. However, it is unclear whether BCDO2 is involved in the formation of the red shell color of clam. To explore the molecular structure and biological function of BCDO2 gene in the process of carotenoids accumulation, in this study, the BCDO2 from hard clam Meretrix meretrix (designated as Mm-BCDO2 ) was cloned and characterized, and the single-nucleotide polymorphisms (SNPs) associated with shell color were detected. The results of qRT-PCR indicated that Mm-BCDO2 gene was expressed in all six tested tissues, and the expression of mantle was significantly higher than other tissues ( P < 0.05). The association analysis identified 20 SNPs in the exons of Mm-BCDO2 , among which three loci (i.e., c.984A > C, c.1148C > T, and c.1187A > T) were remarkably related ( P < 0.05) to the shell color of clam. The western blot analysis revealed that the expression level of Mm-BCDO2 in the mantle of red shell clams was stronger than that of white shell clams ( P < 0.05). Further, the immunofluorescence analysis indicated that the single-layer columnar cells at the edge of the mantle were the major sites for the Mm-BCDO2 secretion. This study explored the potential impacts of BCDO2 gene on the shell color of M. meretrix , which provided a theoretical basis for a better understanding of the important role of BCDO2 in carotenoid metabolism.

PSO-SVM-based deep displacement prediction of Majiagou landslide considering the deformation hysteresis effect - Lei Zhang; Bin Shi; Honghu Zhu; Xiong Bill Yu; Heming Han; Xudong Fan (Landslides, 2021)

HOTAIRM1, an enhancer lncRNA, promotes glioma proliferation by regulating long-range chromatin interactions within HOXA cluster genes - Tengfei Shi; Dianhao Guo; Heming Xu; Guangsong Su; Jun Chen; Zhongfang Zhao; Jiandang Shi; Michelle Wedemeyer; Frank Attenello; Lei Zhang; Wange Lu (Molecular Biology Reports, 2020)